Multidrug resistance associated with glutathione - Budzik, Michał; Badowska-Kozakiewicz, Anna (Menopause Review/Przegląd Menopauzalny, 2013)
Multidrug resistance of cancer cells is one of the most serious barriers to success in cancer disease therapy. Multidrug resistance, i.e. the principal mechanism via which many cancers develop resistance to chemotherapy drugs, is a major factor in the failure of many forms of chemotherapy. The best known mechanism is often attributed to the function of drug transporter proteins in the plasma membrane, which actively remove drugs from neoplastic cells. Abnormal overexpression of these proteins is the most frequently described factor connected with resistance to cytostatics. Among cellular transporter proteins, glycoprotein P (P-gp) plays the most important role. An increased level of this protein is considered a poor prognostic factor in many tumors. Clinical significance of other multidrug resistance proteins remains the subject of intensive studies. Another mechanism to protect the refractory cancer cell against an increasing concentration of cytostatic agents inside the cell is the increased ability to convert the drug into a non-toxic form. An increased activity of detoxifying enzymes such as glutathione transferase, glutathione peroxidase and superoxide dismutase leads to neutralization of the products formed by metabolism of drugs. Recent results of research on ovarian cancer have shown that the factor increasing the risk of this cancer is the presence and expression of the human gene polymorphisms of glutathione S-transferase. High concentrations of glutathione S-transferase is a poor prognostic factor in ovarian cancer and other cancers such as colorectal cancer, lung cancer, stomach cancer, chronic lymphocytic leukemia and gliomas.